Jual Beli Followers Di Media Sosial Instagram Tentang Transaksi Elektronik Dalam Pandangan Hukum Islam - Syaripudin, Enceng Iip; Badruzzaman, Puad (STAI Al Musaddadiyah Garut, 2022)
Instagram is one type of social media that is currently being embraced by various groups. Instagram has become one of the most popular social media platforms in Indonesia. Whether for personal photos, experiences, or important events, or for business purposes such as